2018
DOI: 10.1007/s00394-018-1631-3
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid intake from fruit and vegetables during adolescence is prospectively associated with a favourable risk factor profile for type 2 diabetes in early adulthood

Abstract: Our data indicate that flavonoid consumption from fruit and vegetables during adolescence is associated with a favourable risk factor profile for type 2 diabetes in early adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…On the other hand, fruit was an important polyphenol contributor although the consumption was similar as for vegetables (Table 2). This is in line with the Australian population where apple was the important flavonoid source for young people [14], and the contribution of fruit to flavonoid intake was higher than vegetables' contribution [36].…”
Section: Food Group Contributionssupporting
confidence: 87%
“…On the other hand, fruit was an important polyphenol contributor although the consumption was similar as for vegetables (Table 2). This is in line with the Australian population where apple was the important flavonoid source for young people [14], and the contribution of fruit to flavonoid intake was higher than vegetables' contribution [36].…”
Section: Food Group Contributionssupporting
confidence: 87%
“…One research in Chinese adults also reported that apple was the main food sources of flavonols and flavones [ 23 ]. The present results is in line with the Australian population where apple was the important flavonoid source for young people [ 28 ], and the contribution of fruit to flavonoid intake was higher than that for vegetables [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Mean total flavonoid intake for adolescents (12•5-17•5 years) in the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) study was estimated at 120 mg/4184 kJ per d using two non-consecutive 24-h recalls (10) . Since dietary habits develop during childhood and adolescence, they are considered very important for shaping lifelong dietary habits and the prevention of chronic diseases later in life (11,12) . However, the few studies that described flavonoid intake in children and adolescents are limited to cross-sectional analysis (7,8) , a certain age group (9) , girls (9) , or in the case of isoflavones to Asian populations (13) .…”
mentioning
confidence: 99%